Teaching Education Program and Teaching Experience of Two EFL Teachers: A narrative Inquiry of English Teachers’ Identity - Nainggolan, Bernard Richard (PAEDAGOGIA, 2021)
Previous personal beliefs about teaching, impressions with good teachers, and memories of good teachers might have contributed to motivating students to enroll in the teacher education program. The shape of teacher identity is influenced by students before teaching education programs. However, a question arises on how the teachers’ identity is formed during the teaching education program and how its shift remains to change in the context of teaching at school. My narratives and Puji's were used as the data to answer the research question. This study used the narrative inquiry, which used my narratives and my colleague’s being the primary sources of data. The theories selected, used as the framework, were the ‘Situated Learning’ and the ‘image-text teacher identity. Coding was done to narratives and fundamental concepts were generated. The fundamental concepts of the analyzed data are (1) teacher education program vs teaching experiences, (2) the importance of senior guidance in the learning community, (3) teacher relations as a weapon, (4) affects of a new identity. The findings also show what makes the teacher identity formation different both in the teacher education program and in teaching experience. My study also provides the recommendation for the next research and implications for teacher identity formation.